When Torture Mocks the Law: Understanding Police Brutality in South Africa - Hadebe, Philisiwe; Gopal, Nirmala (International Journal of Criminology and Sociology, 2021)
South Africa promulgated the Prevention and Combating of Torture of Persons Act No. 13 of 2013, which criminalises the use of torture by law enforcers. The Act also criminalises cruel, inhumane, or degrading treatment or punishment of citizens by law enforcers. However, the implementation of this law is derisory as the torture and physical abuse of civilians by the police reportedly continue unabated. This phenomenon seems part of police culture that is entrenched in South African policing practices. Prior to the study, the literature review underscored the unabated prevalence of police violence. Against this background, this article seeks to highlight specific incidences of police officers’ use of unconstitutional and abusive acts of torture involving civilians. Using a qualitative research approach, ten officers of the Independent Police Investigative Directorate (IPID) were interviewed to generate the required data. Thematic analysis was used and the findings revealed that civilians suspected of criminal behaviour were often exposed to inhumane forms of torture, which ranged from food and water deprivation to being strangled, suffocated, and electrocuted. These forms of torture involving suspects were reportedly prompted by the urgency for eliciting information, ‘proving’ the presumption of guilt, proactively preventing crime in communities, and coercing suspect compliance. The findings thus urge the need for a blanket ban on the torture of suspects, the effective investigation by the IPID of cases of torture, and the successful trial and conviction of police perpetrators of this crime.